An unusual choanoflagellate protein released by Hedgehog autocatalytic processing. - Snell, E; Brooke, N; Taylor, W; Casane, D; Philippe, H; Holland, P (2006)
Hedgehog proteins are important cell-cell signalling proteins utilized during the development of multicellular animals. Members of the hedgehog gene family have not been detected outside the Metazoa, raising unanswered questions about their evolutionary origin. Here we report a highly unusual hedgehog-related gene from a choanoflagellate, a close unicellular relative of the animals. The deduced C-terminal domain, Hoglet-C, is homologous to the autocatalytic domain of Hedgehog proteins and is predicted to function in autocatalytic cleavage of the precursor peptide. In contrast, the N-terminal Hoglet-N peptide has no similarity to the signalling peptide of Hedgehog (Hh-N). Instead, Hoglet-N is deduced to be a secreted protein with an enormous threonine-rich domain of unprecedented size and purity (over 200 threonine residues) and two polysaccharide-binding domains. Structural modelling reveals that these domains have a novel combination of features found in cellulose-binding domains (CBD) of types IIa and IIb, and are expected to bind cellulose. We propose that the two CBD domains enable Hoglet-N to bind to plant matter, tethering an amorphous nucleophilic anchor, facilitating transient adhesion of the choanoflagellate cell. Since Hh-C and Hoglet-C are homologous, but Hh-N and Hoglet-N are not, we argue that metazoan hedgehog genes evolved by fusion of two distinct genes.